The Dynamics of Mental Health of the Population of Saudi Arabia during the Covid-19 Pandemic/ Dinamika Kesehatan Mental Penduduk Arab Saudi selama Pandemi Covid-19 - Ruddin, Fajar (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
This study aims to describe the mental health conditions of Saudi Arabian during the Covid-19 pandemic and to analyze the factors that influence it. A qualitative methods through observation, interviews, and collection of qualitative documents were used in this study. The analysis group was divided into three; medical staff, patients and their families, and the general community. The result showed that no serious mass mental problems were found in Saudi Arabia. This was influenced by several factors, including the availability of free psychological counseling services, internalized religious values, and strategic policies adopted by the government.Â Copyright Â© 2020.Â Psikoislamika: Jurnal Psikologi dan Psikologi Islam